Strategi Guru Pendidikan Agama Islam Dalam Pembinaan Akhlakul Karimah Siswa di SMP Islam Nurul Ulum Kecamatan Mumbulsari Kabupaten Jember - Azizah, Fabrul; Irawan, Vaesol Wahyu Eka; Slamet, Slamet (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) STIB Banyuwangi, 2023)
This study describes the moral development program at SMP Islam Nurul Ulum, the approaches and steps used by Islamic Religious Education teachers, and the supporting and inhibiting factors in fostering students' morals. The method used is qualitative with data collection techniques through observation, interviews, and documentation. Data analysis uses the Miles and Huberman model, including data reduction, data presentation, and conclusions. The study results indicate that SMP Islam Nurul Ulum has a moral development program that includes relationships with Allah, fellow human beings, the environment, and oneself. The teacher's approach is carried out directly, such as providing personal guidance and advice, and indirectly through prevention and punishment. Supporting factors for moral development include student awareness, teacher role models, learning methods, and parental support and facilities. Meanwhile, inhibiting factors include lack of Islamic Religious Education lessons, use of mobile phones, lack of communication, and the environment and background of students that do not support.